2015
DOI: 10.1177/2156587215590232
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Efficacy of an Herbal Compound on Dry Mouth in Patients With Head and Neck Cancers

Abstract: Dry mouth is a common complication of radiotherapy for head and neck cancers. This study compared the efficacy of an herbal compound containing Malva sylvestris and Alcea digitata (Boiss) with artificial saliva (Hypozalix) for improving the symptoms of dry mouth in head and neck cancer patients. The study examined a total of 62 subjects assigned to 2 groups. The herbal compound and Hypozalix were administered for 4 weeks. Efficacy was assessed using the visual analog scale and by grading the degree of dry mout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 12 publications
(17 reference statements)
1
49
0
1
Order By: Relevance
“…One open-label parallel study assessed the effectiveness of four-week use of an herbal compound containing Malva sylvestris and Alcea digitata powder compared to artificial saliva (Hypozalix) [24]. No objective measures were used in this study, however the visual analogue score showed a significant differences between the two treatment in lessening xerostomia symptoms.…”
Section: Herbal Compound Vs Salivary Substitutementioning
confidence: 99%
See 1 more Smart Citation
“…One open-label parallel study assessed the effectiveness of four-week use of an herbal compound containing Malva sylvestris and Alcea digitata powder compared to artificial saliva (Hypozalix) [24]. No objective measures were used in this study, however the visual analogue score showed a significant differences between the two treatment in lessening xerostomia symptoms.…”
Section: Herbal Compound Vs Salivary Substitutementioning
confidence: 99%
“…Table 2 shows study populations, interventions, and extracted outcome measures for eligible trials. Seventeen studies used changes in xerostomia symptoms as an outcome; outcome measures included the visual analogue scale (nine studies) [17][18][19][20][21][22][23][24][25], the xerostomia inventory (one study) [26], the Walizer Mouth Dryness questionnaire (one study) [27], the global rating of change scale (two studies in one paper) [28], general xerostomia questionnaires (two studies) [29,30], and the xerostomia items of the European Organization for Research and Treatment of Cancer Quality of Life Head and Neck Module (EORTC-H&N35) instrument (two studies) [31,32]. At endpoint, symptoms were assessed shortly after administration of the intervention in three studies [28,29], and after 180 minutes in one trial [19], and therefore refer to symptoms perceived by participants during enhancement of salivary gland function.…”
mentioning
confidence: 99%
“…The antioxidant (21), anti-inflammatory (22), and antimicrobial (23,24) effects of these plants were investigated in the recent studies. Also, it was shown that A.digitata and M.sylvestris are mucilaginous plants that can be used to improve dry mouth (25).…”
Section: Discussionmentioning
confidence: 99%
“…Результаты мультицентрового рандомизированного двойного слепого клинического исследования, результа-ты которого опубликованы в 2015 г. в журнале EvidenceBased Complementary & Alternative Medicine («Альтерна-тив ная и дополнительная доказательная медицина»), показали высокую эффективность спрея искусственной слюны по сравнению с гомеопатическими средствами у онкологических больных [50].…”
Section: таблица частота выявления ксеростомии при некоторых системнunclassified